Investigation the performance of modified watermelon skin to adsorb humic acid from aqueous solutions - Mohammad Pirbavehpour; Bahareh Lorestani; Maryam Kiany Sadr; Mehrdad Cheraghi; Atefeh Chamani (Muhandisī-i Bihdāsht-i Muḥīṭ, 2023)
Background: The abundance of humic substances in nature and their entry into water resources cause changes in color, taste and smell in water. which makes a huge amount of water in the world useless, Recently various methods have been presented to remove natural organic substances from water. But surface adsorption has a high removal capacity compared to the other methods. In this research the performance of modified watermelon skin in adsorption of humic acid from aqueous solutions on a continuous scale have been investigated. Methods: In this study, the effect of different parameters such as contact time, activation temperature,pH, adsorbent dose, initial concentration and ionic strength and thermodynamics on humic acid removal efficiency were investigated.Using SEM spectrum (scanning electron microscope) the appearance characteristics of the adsorbent were done. Humic acid concentration was determined using spectrophotometer in 254 nm wavelength. findings: Results of the research showed that the highest amount of removal occurs in acidic environment, By increasing time and adsorbent dose and decreasing the initial concentration, the removal efficiency of humic acid increased for example:in time(45 minutes) and PH=4 and amount of adsorbent(0.1 g.L-1) with concentration removal is (50 mg.L-1) and the maximum removal of humic acid reached (90.98%) and the humic acid adsorption thermodynamically is an endothermic process. Conclusion: Activated carbon produced from watermelon skin as a new adsorbent from agricultural wastes is very effective in removing humic organic substances due to its abundance, low price and high efficiency.